2021
DOI: 10.3390/nu13041138
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Parental Dietary Behaviors and Practices on Children’s Eating Habits

Abstract: Poor dietary habits established during childhood might persist into adulthood, increasing the risk of developing obesity and obesity-related complications such as Type 2 Diabetes Mellitus. It has been found that early modifications in eating habits, especially during childhood, might promote health and decrease the risk of developing diseases during later life. Various studies found a great influence of parental dietary habits on dietary behaviors of their children regardless of demographic characteristics suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
119
2
15

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 178 publications
(141 citation statements)
references
References 82 publications
5
119
2
15
Order By: Relevance
“…Interpersonal relationships serve as a significant factor influencing eating behavior through social influence, and bad interpersonal relationships are even one of the main factors for eating disorders [14,15]. There exists an important influence on eating behavior among family members such as spouses, offspring, and siblings [16][17][18]. Additionally, there is ample evidence that social and community environment, including residence, education, career, and income, has a powerful effect on eating behavior such as food choice and amounts consumed [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Interpersonal relationships serve as a significant factor influencing eating behavior through social influence, and bad interpersonal relationships are even one of the main factors for eating disorders [14,15]. There exists an important influence on eating behavior among family members such as spouses, offspring, and siblings [16][17][18]. Additionally, there is ample evidence that social and community environment, including residence, education, career, and income, has a powerful effect on eating behavior such as food choice and amounts consumed [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, while snacking results in postprandial hyperglycemia, snacking habits, through the continued consumption of unhealthy snacks, produce hepatic and peripheral insulin resistance, which further worsens the hyperglycemia. Since the strength of habits is the most important predictor in explaining unhealthy snack intake [ 17 ] and since poor dietary habits established during childhood could persist into adulthood, which increases the risk of developing obesity and obesity-related complications such as type 2 diabetes [ 18 ], it is important to encourage the development of healthy eating habits as early as possible so that they can last a lifetime.…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that parents’ eating habits and food preferences play an important role in shaping food intake patterns in children [ 5 ] as children consider their parents as role models. Previous studies suggested that parents who are “healthy role models” would be more likely to have children who consume healthier foods [ 6 , 7 ]. Moreover, parents were found to have a strong influence over the family environment where meals take place and the types and portions of foods provided to children [ 8 ].…”
Section: Introductionmentioning
confidence: 99%